Independensi Auditor Berbasis Taro Ada Taro Gau' Dalam Meningkatkan Kualitas Audit - Astridani, Andi; Abdullah, Muhammad Wahyuddin; Jannah, Raodahtul (ISAFIR: Islamic Accounting and Finance Review, 2024)
This paper aims to determine the independence of auditors at KAP Ardaniah Abbas, and relate it to the Bugis principle of Taro Ada Taro Gau’ then to determine the improvement of audit quality with auditor independence based on Taro Ada Taro Gau’ at KAP Ardaniah Abbas. The results of the study concluded that auditor independence at KAP Ardaniah Abbas plays an important role in determining the quality and reliability of audit results. In essence, this independence reflects the auditor's capacity to carry out their duties without any influence or pressure that can affect their objectivity. The combination of honest, consistent, and careful attitudes or in the Bugis principle of Taro Ada Taro Gau’ creates an atmosphere in which auditor independence can be maintained. The Bugis principle of Taro Ada Taro Gau’ which is based on an attitude of independence forms a strong foundation for reliable and quality audit practices..